Practice of Banking Vol.2 : lending and finace - Osayameh, Ralph K.O. (Lagos : Collins Publishing, 1986)
The book combines theory with practice and uses case studies to highlight practical lending situations as well as progress questions designed to gauge the level of understanding in each chapter
Includes bibliography, index
osc 27/4/18
Loans
Keywords: Bank Management